Contradictory Results of the GULAG Activities in the European North-East of the USSR - Maksimova, Liubov Anatoljevna (Journal of History Culture and Art Research, 2019)
The author outlines the conflicts in the actions of the GULAG in the Soviet European north-east. Mobilization facilities of the GULAG allowed creating fuel and energy sources in the North-East of the country in short terms. Due to the GULAG, industries were being developed in the district without any prerequisites. Activities of the victimized population produced fulfillment of important innovative projects at the world level for that time. Primitive methods were often used for the creation of ambitious and high-tech projects with a great portion of manual labor. Forced migration brought about growth in population in the district, forced growth in the urban population, and rapid development of the area. Meanwhile, urbanization process proceeded spontaneously, without taking into consideration some of the possible negative effects of towns’ development having appeared at the camp centers. The need to relocate population from the North is a serious modern problem dating back to the GULAG. Industrial development of the area was followed by the attempt at making life of the locals a little bit more civilized: the victimized population created a health-care system in the Northern districts of the Komi Republic, as well as a personnel-training system, cultural institutions (theaters, social clubs, libraries, publishing houses) and education. Besides, a drastic change in the way of life of the locals under the impact of the GULAG economic activities brought about the destruction of the traditional way of life, loss of self-identity, and transformation of traditional morality. The industrial processes fulfilled by the GULAG were accompanied by the formation and development of the system of training skilled personnel for industries and transportation. At the same time, the wasteful squandering of the skilled prisoners’ abilities and talents occurred in the GULAG camps. The concentration of the labor force in the GULAG camps in the region encouraged the exploration of natural resources in the area in the short term and resulted in a developed economy. At the same time, the development by the camp method caused irreparable injury to the nature of the region. The camps’ economic activities led to the formation of new advanced industrial branches, transportation system, and social infrastructure as modernization phenomena. However, the totalitarian regime did not allow the introduction of the elements of the classical liberalism in the modernization processes. Industrial modernization was carried out by means of coercive labor, deprived of their civil rights, alongside with the lack of democratic values. Modernization was halved and pared-down.